Application Of Safe And Efficient Control Methods Using Odd-Numbered Fuzzy Logic Elements For Small Hydropower Plants (Texas Journal of Engineering and Technology, 2025)
Many factors associated with streamflow are vague, subjective, and difficult to quantify. The fuzzy logic method is very useful for such an approach to solving problems as small hydropower. The performance of a fuzzy linguistic variable can easily be characterized in general terms. The paper initially presents a new fuzzy logic controller (FLC) method for the safe control of dam reservoirs through spillway gates.